Folklore Linguistics Origins in the Works of O. O. Potebnya - Сердега, Руслан Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
Today any researcher of language can’t do without works of the representative of the Kharkiv philological school O. O. Potebnya. The scientist paid great attention to issues related to the study of folklore language. Oleksandr Opanasovych Potebnya can be called a forerunner of the Ukrainian folklore linguistics. An outstanding philologist considered the language of folklore as a source of world outlook, mentality, mental state, and the history of the people. The article reviews and analyzes the works in which O. O. Potebnya actually laid the foundation of modern folklore linguistics. The Kharkiv linguist set forth integral studies about nature of word and poetic work. This doctrine has absorbed the achievements of European intellectual thought. O. O. Potebnya considered a large number of folklore texts. A scientist became familiar with to work from collection of folklore. He collected the standards of folklore texts on Slobozhanschyna. However these standards were published only in ХХ century. The Large merit of O. O. Potebnya consists in that he gave to us the standards of analysis of language units taking into account etymology, analogies in other languages, contextual surroundings, intercommunication of facilities of expression. The prognostic character of row of ideas of scientist, in particular, and in industry of study of verbal folk literature, predetermines the urgent necessity of the new reading him scientific works.